Comparison of Mangrove and Coastal Ecosystem Management Strategies between Padang City (Indonesia) and Port Dickson (Malaysia) to Support Coastal Resilience - Fardilla, Midratul; Salsabila, Ilham; Aswin, Zeus Marullah; Fadila; Akbarullah; Kamal, Eni; Dewata, Indang; Syah, Nurhasan; Fatimah, Siti; Barlin, Eri; Heldi; Umar, Iswandi (Maritime Park: Journal of Maritime Technology and Society, 2026)
Mangrove and coastal ecosystems play a critical role in enhancing coastal resilience; however, their effectiveness strongly depends on governance arrangements and management strategies. This study applies a qualitative comparative case study approach integrating a Systematic Literature Review (SLR) and field observations to compare mangrove and coastal ecosystem management strategies in Padang City (Indonesia) and Port Dickson (Malaysia). A structured comparative framework was used to assess biophysical conditions, governance structures, monitoring capacity, community participation, and contributions to ecological, institutional, and social resilience. The results indicate that Padang City possesses larger mangrove extent and higher species diversity, supporting stronger ecological and social resilience, but is constrained by fragmented governance and weak enforcement. Port Dickson exhibits smaller and fragmented mangrove areas with clearer institutional authority and periodic monitoring, yet limited social–ecological integration. The findings highlight that effective coastal resilience requires integrating strong regulatory frameworks, community engagement, and consistent long-term monitoring.